Variable speed pumped hydro storage: A review of converters, controls and energy management strategies - Vasudevan K.R.; Ramachandaramurthy V.K.; Venugopal G.; Ekanayake J.B.; Tiong S.K. (Elsevier Ltd, 2023)
Digital storage; Energy management systems; Energy storage; Maximum power point trackers; Stochastic systems; Converter controls; Management strategies; Maximum Power Point Tracking; Microgrid; Power; Power generation mix; Pumped hydro storage; Renewables; Storage systems; Variable speed; Energy management